RIVER MEANDERS ON ALLUVIAL PLAINS AND HILLY TOPOGRAPHY - Raharjo, Puguh Dwi; Haryono, Eko; Setiawan, Muhammad Anggri; Permana, Haryadi (Journal of Environmental Science and Sustainable Development, 2023)
Previous research on meandering rivers in Indonesia, precisely in Java, has predominantly focused on alluvial plains, while their presence is also observed in hilly regions with rocky substrates. The study aims to investigate different meandering types in Java and establish regional connections between these types and geological and geomorphological processes. The methodology involves identifying high-resolution remote sensing images and topographic data, followed by analysis based on geological and geomorphological developments. To categorize the rivers, sinuosity ratios are meticulously calculated. The tectonic setting, which influences physiography and geomorphology, is an analytical unit for determining the meandering process. The result reveals that meandering rivers are primarily located in the alluvial plains of northern Java. Meanwhile, meandering rivers in hilly areas are concentrated in structural formations, predominantly in southern and central Java. In alluvial plains, meandering rivers display a regular pattern with higher concentrations of curvature downstream, and their substrates consist of deposits or soil. Conversely, meandering rivers in hilly regions exhibit irregular and winding patterns, randomly distributed from upstream to downstream. These rivers are situated in the physiographic regions of Southern Mountains, Hills in Central Depression, and Kendeng Hills, and their substrates mainly comprise rocks, leading to a more protracted process of curvature transformation. In conclusion, meandering rivers in Java can form not only in alluvial plains but also in hilly areas. Meanders on hilly topography possess higher sinuosity ratios than those on alluvial plains, displaying irregular patterns. Energy minimization alone is not the sole controlling factor; the physical surface conditions also play a significant role, particularly in meanders in hilly areas, resulting in a diverse typology of meanders. Therefore, understanding the formation of meandering rivers in various topographic regions can serve as a basis for policymaking, particularly in flood mitigation and riverbank erosion management.